Association of Transforming Growth Factor β1 Gene Polymorphisms and Asbestos-Induced Fibrosis and Tumors. (1st June 2009) - Helmig, Simone; Belwe, Alexandra; Schneider, Joachim
Abstract : Aim: Inhaled asbestos fibers are known to cause progressive lung or pleural fibrosis and malignancies such as lung cancer or diffuse malignant mesothelioma. Transforming growth factor β1 (TGF-β1), a multifunctional cytokine, regulates the proliferation and differentiation of cells. Transforming growth factor β1 is known to promote the pathogenesis of lung fibrosis and acts as a tumor suppressor in normal cells. Two genetic polymorphisms in codons 10 (Leu10Pro) and 25 (Arg25Pro) of the TGF-β1 gene are suggested to be associated with a different TGF-β1 protein production. Therefore, we examined an association between the 2 TGF-β1 gene polymorphisms and asbestos-induced lung fibrosis and lung cancer. Methods: Detection of the 2 polymorphisms was performed by rapid capillary polymerase chain reaction, with melting curve analysis, using fluorescence-labeled hybridization probes. To investigate the association between TGF-β1 gene polymorphisms in codons 10 and 25 and the susceptibility to asbestos-induced diseases, association studies were performed with healthy control subjects (n = 83), patients with pulmonary fibrosis (n = 591), and patients with bronchial carcinoma (n = 147). Results: Compared with a healthy control group, odds ratio (OR) analysis revealed an inverse relationship for the proline allele at codon 10 or 25 with pulmonary fibrosis (higher risk) and lung cancer (lower risk). The proline allele at codon 10 or 25 is significantly associated with a higher risk for fibrotic lung diseases (ORcrude, 1.46; 95% confidence interval [CI], 1.01-2.11; P = 0.045 and ORadjusted, 1.76; 95% CI, 1.14-2.72; P = 0.011, respectively, for codon 10; OR, 2.13; 95% CI, 1.33-3.99; P = 0.019 and ORadjusted, 2.27; 95% CI, 1.14-4.52; P = 0.02, respectively, for codon 25) when compared with patients with lung cancer. A significant association for the proline allele is also revealed when comparing patients with asbestosis (ORcrude, 3.01; 95% CI, 1.44-6.29; P = 0.003 and ORadjusted, 3.72; 95% CI, 1.56-8.85; P = 0.011) with patients with asbestos-induced lung cancer. Conclusions: In summary, the results confirm the hypothesis that TGF-β1 polymorphisms are associated with asbestos-induced fibrotic or malignant lung diseases in whites.